Gender differences and gender convergence in alcohol use over the past three decades (1984-2008), The HUNT Study, Norway - Grete Helen Bratberg; Sharon C Wilsnack; Richard Wilsnack; Siri Håvås Haugland; Steinar Krokstad; Erik Reidar Sund; Johan Haakon Bjørngaard (BMC, 2016)
Abstract Background To examine changes in men's and women's drinking in Norway over a 20-year period, in order to learn whether such changes have led to gender convergence in alcohol drinking. Methods Repeated cross-sectional studies (in 1984-86, 1995-97, and 2006-08) of a large general population living in a geographically defined area (county) in Norway. Information about alcohol drinking is based on self-report questionnaires. Not all measures were assessed in all three surveys. Results Adult alcohol drinking patterns have changed markedly over a 20-year period. Abstaining has become rarer while consumption and rates of recent drinking and problematic drinking have increased. Most changes were in the same direction for men and women, but women have moved towards men's drinking patterns in abstaining, recent drinking, problematic drinking and consumption. Intoxication (among recent drinkers) has decreased in both genders, but more in men than in women. The declines in gender differences, however, were age-specific and varied depending on which drinking behavior and which beverage was taken into account. Conclusions There has been a gender convergence in most drinking behaviours, including lifetime history of problem drinking, over the past 2-3 decades in this Norwegian general population, but the reasons for this convergence appear to be complex.